KESADARAN HUKUM, PSYCHO ADVERTISING DAN PSYCHOPRENEURSHIP - Divania Fazrina; Maharani Amelia Firjatullah, Afrizal Qimas Chairi, Isna Faradilla, Al Fachri Nurfath, Evani Alvi Nug (Adiba Aisha Amira, 2024)
The